2008
DOI: 10.4049/jimmunol.180.10.6885
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Proinflammatory Response to Francisella tularensis Live Vaccine Strain Requires Coordination of Multiple Signaling Pathways

Abstract: The macrophage proinflammatory response to Francisella tularensis (Ft) live vaccine strain (LVS) was shown previously to be TLR2 dependent. The observation that intracellular Ft LVS colocalizes with TLR2 and MyD88 inside macrophages suggested that Ft LVS might signal from within the phagosome. Macrophages infected with LVSΔiglC, a Ft LVS mutant that fails to escape from the phagosome, displayed greatly increased expression of a subset of TLR2-dependent, proinflammatory genes (e.g., Tnf) but decreased expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
104
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 45 publications
15
104
2
Order By: Relevance
“…Thus, both IglG, to some extent, and, even more so, IglI are important for the IL-1␤ release by LVS, consistent with their delayed escape from the phagosomes. Thus, as suggested previously, there is a strong correlation between production of active IL-1␤ protein and a cytoplasmic location of the bacterium (4,21,28,38).…”
Section: Vol 79 2011mentioning
confidence: 50%
See 2 more Smart Citations
“…Thus, both IglG, to some extent, and, even more so, IglI are important for the IL-1␤ release by LVS, consistent with their delayed escape from the phagosomes. Thus, as suggested previously, there is a strong correlation between production of active IL-1␤ protein and a cytoplasmic location of the bacterium (4,21,28,38).…”
Section: Vol 79 2011mentioning
confidence: 50%
“…F. tularensis phagosomal escape into the macrophage cytosol is critical for the inflammasome-dependent induction of IL-1␤ secretion (4, 21, 28, 38, 52). Consequently, macrophages infected with strains with mutations in mglA, iglC, vgrG, or iglI have been shown to display abrogated IL-1␤ release (4,21,28,38,76). To determine whether PdpE, IglG, and IglI play a role in this process, we measured the concentration of IL-1␤ in culture supernatants of macrophages infected with the corresponding LVS mutants at 0, 5, 8, or 24 h postinfection.…”
Section: Vol 79 2011mentioning
confidence: 99%
See 1 more Smart Citation
“…These observations, coupled with the observation that TNF and IL-6 expression are completely dependent on p38 and/or ERK1/2 activity, strongly suggest that the increased cytokine levels in response to inhibition of PI3K result from enhanced and sustained MAPK activation. Importantly, wortmannin treatment did not inhibit bacterial uptake, which could potentially lead to sustained TLR signaling at the macrophage surface or in the phagosome (27). PI3K has also been shown to suppress proinflammatory cytokine production in human monocytes and PBMCs in response to various defined TLR ligands by inhibiting GSK3b activity (48).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TLR2-dependent proinflammatory cytokine responses in the lung are significantly delayed (7,8), and several in vitro studies have suggested that F. tularensis can directly inhibit proinflammatory signaling in infected macrophages and dendritic cells (7,9,10,26). Although progress has been made in understanding the roles of TLRs and other PRRs (27)(28)(29) in recognizing F. tularensis, little is known about how F. tularensis modulates PRR signaling to its advantage during infection. The PI3K/Akt pathway has emerged as an important regulator of innate immune responses.…”
mentioning
confidence: 99%